Prevalence and incidence of reactions to insect stings in children: a reappraisal - Quercia, O; Incorvaia, C; Marseglia, G L; Puccinelli, P; Dell'albani, I; Emiliani, F; Frati, F; Stefanini, G F (Minerva pediatrica, 2014)
The prevalence of systemic reactions (SR) to Hymenoptera stings in children was estimated in values lower than 1% in early studies but much higher in recent surveys. We evaluated the current prevalence and the incidence of SR and large local reactions (LLR) to Hymenoptera stings in children in Italy. The data on children were collected from the database of the population study on the city of Cotignola, analyzing the answers to the part of the questionnaire about Hymenoptera stings, that concerned if the subject was ever stung by apids or vespids, if there has been a SR or a LLR, and if subjects with reactions received a diagnostic evaluation and a medical treatment. Of the population of 1035 children, 173 (16.7%) were stung at least one time by Hymenoptera. Of them, 5 had had a SR and 9 had had a LLR. This defines a prevalence of SR of 0.5% and of LLR of 0.9%. Only one reaction was severe. Of the 14 subjects with SR or LLR, 5 (35.7%) underwent a diagnostic evaluation and one (7.1%) was treated with venom immunotherapy. The incidence of SR in the subsequent 2 years was 0.09% in the first year and 0.08% in the second year. These findings do not confirm the recent reports of an increased prevalence of Hymenoptera venom allergy in children. The incidence of SR to stings, thus far unreported for children, was very low both in the first and in the second year.